A New Insight of Anti‐Solvent Electrolytes for Aqueous Zinc‐Ion Batteries by Molecular Modeling. Issue 4 (13th January 2023) - Zhu, Yilong; Hao, Junnan; Huang, Yan; Jiao, Yan
Abstract : Aqueous zinc‐ion batteries (AZIBs) have attracted wide attention for large‐scale energy storage. However, the practical application of AZIBs is limited by the poor reversibility of Zn anodes. Recently, a strategy of adding low‐cost anti‐solvent to electrolytes is proposed experimentally, which can improve Zn reversibility therefore the AZIBs performance. Nevertheless, the mechanism of the strategy remains elusive, especially how the Zn reversibility is improved and why various anti‐solvents perform differently. Herein, atomic‐level insight into the mechanism, is provided, by modeling ZnSO4 electrolytes with different anti‐solvents, that is, methanol and ethanol. Through molecular dynamics simulations and density‐functional theory calculations, how anti‐solvents impact Zn 2+ solvation sheath and water activity is explored. It is suggested in the results that methanol promotes Zn reversibility for two reasons. First, methanol can modify the Zn 2+ solvation sheath to reduce the energy barrier for Zn 2+ de‐solvation. Second, methanol can form H‐bond with water molecules to suppress H2 evolution. Based on the new atomic level insight, herein, the practical universality of the anti‐solvent strategy is confirmed in other aqueous batteries for developing more effective anti‐solvents. Abstract : Herein, atomic level insight to a low‐cost anti‐solvent strategy is provided to promote aqueous zinc‐ion batteries using molecular dynamics simulation and density‐functional theory calculation.